The supplement, at the border between food and medicine - Andreea Loredana Savancea; Maria Crivineanu; Diana Mihaela Alexandru (Medicamentul Veterinar)
This article aims to explore the uncertain legal status of animal supplements, positioned at the intersection between feed and medicine, from the perspective of both European and national legislation. According to European law, the term "animal dietary supplement" is not used in the context of veterinary products; instead, such products are classified as either complementary feed or feed additives. While feed intended for farm animals is strictly regulated under Regulations (EC) No. 183/2005, pet food is excluded from this provision, resulting in a significant legislative gap. This exclusion means that supplements for companion animals are not subject to the same stringent requirements regarding safety, traceability, and quality control. Furthermore, these supplements are not clearly categorized as either feed or medicine, which complicates the processes of authorization and commercialization. This paper analyzes these inconsistencies and highlights the need for clear legislation to govern animal supplements, ensuring uniform standards of safety and efficacy.